Perioperative fluid maintenance in young children with urgent abdominal pathology - V.I. Snisar; S.V. Egorov; O.S. Pavlish (Zaslavsky O.Yu., 2020)
Safe fluid therapy in children requires deep knowledge of main principles, which are based on water-electrolyte metabolism and acid-base balance in childhood. Water and electrolyte content in children's body is supported within very narrow limits, that is why it is very important to understand the potential physical effects of imbalances in water and substances dissolved in it because these changes always occur in the perioperative period. Perioperative fluid therapy directly impacts the clinical outcome of treatment, and therefore its appointment should meet the needs of a patient. The goal of fluid therapy in sick children in the perioperative period is to maintain effective circulating volume and to prevent, where possible, interstitial fluid overload. Besides the knowledge of the physiology and pathophysiology of water-electrolyte metabolism in childhood, an adequate fluid therapy requires an understanding of the pharmacology of infusion drugs, their dosage, techniques of use, violations of which may adversely affect the prognosis of the disease. That is why the purpose of our research is to study changes of hemodynamic indicators, water-electrolyte and acid-base metabolism while using various infusion solutions in the perioperative period. This work was done based on the analysis of the treatment of 55 pediatric patients with urgent abdominal pathology, which, depending on the type of perioperative infusion therapy conducted were divided into 3 groups. The 1st group covered the children who received as perioperative infusion therapy with hypotonic glucose-salt solutions, the 2nd group involved the children who had been treated with Ringer's lactate solution, the 3rd group consisted of the children treated with a balanced electrolyte Ringer's malate solution. This research showed that children with urgent abdominal pathology had dehydration and absolute hypovolemia, which worsened due to the development of hypoosmotic conditions. The quick normalization of hemodynamic parameters, water-electrolyte metabolism, acid-base balance and water sectors of a body needs an optimal infusion medium - a balanced saline solution with aspartate and malate added.